Thinking Ahead: Continual Computation Policies for Allocating Idle and Real-Time Resources to Solve Future Challenges - Horvitz, Eric (Proceedings of IJCAI '99, Sixteenth Joint Conference on Artificial Intelligence, Stockholm, Sweden, 1999)
Research on continual computation centers on developing precomputation policies that can effectively harness available resources to solve future challenges. We focus on integrating a consideration of offline and real-time resources in continual computation. We review precomputation policies for flexible procedures and present strategies that account for the expected future real-time refinement of a result following precomputation. Finally, we address policies that consider the tradeoff between the efficiency of solving current and potential future challenges.